Extended resuscitative endovascular balloon occlusion of the aorta (REBOA)-induced type 2 myocardial ischemia: a time-dependent penalty. Issue 1 (31st January 2019) - Wasicek, Philip J; Teeter, William A; Yang, Shiming; Banchs, Hector; Galvagno, Samuel M; Hu, Peter; Gamble, William B; Hoehn, Melanie R; Scalea, Thomas M; Morrison, Jonathan J
Abstract : Background: Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) increases cardiac-afterload and is used for patients in hemorrhagic shock. The cardiac tolerance of prolonged afterload augmentation in this context is unknown. The aim of this study is to quantify cardiac injury, if any, following 2, 3 and 4 hours of REBOA. Methods: Anesthetized swine (70–90 kg) underwent a 40% controlled hemorrhage, followed by supraceliac resuscitative endovascular balloon occlusion of the aorta (REBOA) for 2 (n=5), 3 (n=5), and 4 hours (n=5). High-fidelity arterial wave form data were collected, and signal processing techniques were used to extract key inflection points. The adjusted augmentation index (AIx@75; augmentation pressure/pulse pressure, normalized for heart rate) was derived for use as a measure of aortic compliance (higher ratio = less compliance). Endpoints consisted of electrocardiographic, biochemical, and histologic markers of myocardial injury/ischemia. Regression modeling was used to assess the trend against time. Results: All animals tolerated instrumentation, hemorrhage, and REBOA. The mean (±SD) systolic blood pressure (mm Hg) increased from 65±11 to 212±39 (p<0.001) during REBOA. The AIx@75 was significantly higher during REBOA than baseline, hemorrhage, and resuscitation phases (p<0.05). A time-dependent rise in troponin (R 2 =0.95; p<0.001) and T-wave deflection (R 2 =0.64; p<0.001) was observed. The maximum mean troponin (ng/mL) occurred at 4 hours (14.6±15.4) and maximum T-wave deflection (mm) at 65 minutes (3.0±1.8). All animals demonstrated histologic evidence of acute injury with increasing degrees of cellular myocardial injury. Discussion: Prolonged REBOA may result in type 2 myocardial ischemia, which is time-dependent. This has important implications for patients where prolonged REBOA may be considered beneficial, and strategies to mitigate this effect require further investigation. Level of evidence: II.